On‐the‐Job Reference Materials. Issue 5 (6th May 2019) - Unknown
Abstract : This is an abridged excerpt from Manual of Water Supply Practices M32, Computer Modeling of Water Distribution Systems, fourth edition (catalog No. 30032‐4E). The book is available from the AWWA Store (https://store.awwa.org ).